Finite Element Simulation of the Compaction and Springback of Alumix 321 PM Alloy. (30th September 2015) - Selig, Stanley G.; Doman, Darrel A.
Abstract : A finite element simulation of the compaction and springback of an aluminum-based powder metallurgy alloy (Alumix 321) was developed and validated using the LS-DYNA hydrocode. The present work aims to directly address the current scarcity of modeling works on this popular alloy system. The Alumix 321 constitutive material parameters are presented. The model can predict the results of single-action compaction as well as the amount of springback experienced by a compact upon ejection from the die. The model has been validated using a series of experiments including powder compaction, optical densitometry, and the creation of a compaction curve.